Psychophysical study of face identity discrimination in schizophrenia: association with facial morphology. Issue 6 (1st November 2016) - Ekstrom, Tor; Maher, Stephen; Chen, Yue
ABSTRACT: Introduction: Identifying individual identities from faces is crucial for social functioning. In schizophrenia, previous studies showed mixed results as to whether face identity discrimination is compromised. How a social category factor (such as gender and race) affects schizophrenia patients' facial identity discrimination is unclear. Methods: Using psychophysics, we examined perceptual performance on within- and between- category face identity discrimination tasks in patients ( n = 51) and controls ( n = 31). Face images from each of six pairs of individuals (two White females, two White males, two Black males, two Asian females, one Black male and one White male, and one White female and one White male) were morphed to create additional images along a continuum of dissimilarity in facial morphology. Results: Patients underperformed for five out of the six face pairs (the Black/White male pair was the exception). Perceptual performance was correlated with morphological changes in face images being discriminated, to a greater extent in patients than in controls. Conclusions: Face identity discrimination in schizophrenia was most impaired for those faces that presumably have extensive social exposures (such as White males). Patients' perceptual performance appears to depend more on physical feature changes of faces.